Study on pyrolysis of sagwan (tectona grandis) sawdust and use of biochar for aqueous cr(vi) removal - Gupta, Goutam Kishore (IIT(BHU) Varanasi, 2020)
Abstract is available in content.
Keywords: pyrolysis of sagwan; sawdust; biochar for aqueous